2021
DOI: 10.3390/diagnostics11122349
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Heart Sound Analysis for Left Ventricular Diastolic Dysfunction Diagnosis

Abstract: The aggravation of left ventricular diastolic dysfunction (LVDD) could lead to ventricular remodeling, wall stiffness, reduced compliance, and progression to heart failure with a preserved ejection fraction. A non-invasive method based on convolutional neural networks (CNN) and heart sounds (HS) is presented for the early diagnosis of LVDD in this paper. A deep convolutional generative adversarial networks (DCGAN) model-based data augmentation (DA) method was proposed to expand a HS database of LVDD for model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In the reviewed literature, most studies use CNN models with 2 to 34 convolutional layers [9, 10, 11, 13, 14, 15, 18, 21, 22, 23, 24, 25, 26, 27, 28, 31, 32, 33, 34, 35, 37, 38, 40, 41, 42, 47, 48, 50, 51, 52, 55, 58, 59, 60, 61, 68, 69, 71, 72, 73, 84], which are usually equipped with rectified linear units, batch normalization, dropout and pooling components, and some of the layers are linked by residual connections. Wang et al [76] test 10 different CNN models including GoogleNet, SqueezeNet, DarkNet19, ModileNetv2, Inception-ResNetv2, DenseNet201, Inceptionv3, ResNet101, NasNet-Large, and Xception to compare the performances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the reviewed literature, most studies use CNN models with 2 to 34 convolutional layers [9, 10, 11, 13, 14, 15, 18, 21, 22, 23, 24, 25, 26, 27, 28, 31, 32, 33, 34, 35, 37, 38, 40, 41, 42, 47, 48, 50, 51, 52, 55, 58, 59, 60, 61, 68, 69, 71, 72, 73, 84], which are usually equipped with rectified linear units, batch normalization, dropout and pooling components, and some of the layers are linked by residual connections. Wang et al [76] test 10 different CNN models including GoogleNet, SqueezeNet, DarkNet19, ModileNetv2, Inception-ResNetv2, DenseNet201, Inceptionv3, ResNet101, NasNet-Large, and Xception to compare the performances.…”
Section: Resultsmentioning
confidence: 99%
“…At last, 71 original articles were included. These studies can be broadly categorized into several groups: methods (15 papers, including heart sound segmentation [6, 7, 8, 9, 10, 11, 12, 13], noise cancellation [14, 15, 16], algorithm development [17, 18, 19], and database development [20]), cardiac murmurs detection (36 papers [21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56]), valvular heart disease (6 papers [57, 58, 59, 60, 61, 62]), congenital heart disease (4 papers [63, 64, 65, 66]), heart failure (4 papers [67, 68, 69, 70]), coronary artery disease (2 papers [71, 72]), rheumatic heart disease (2 papers [73, 74]), and extracardiac applications (2 papers [75, 76]).…”
Section: Methodsmentioning
confidence: 99%
“… 11 Convolutional neural network trained with a short-time Fourier transform spectrum is reported to show 99% of sensitivity and specificity in distinguishing LV diastolic dysfunction ( n = 30) from healthy controls ( n = 41). 10 The LV diastolic dysfunction group was a mixture of HFrEF and HFpEF patients (LVEF: 45% ± 16%) with a high E / e ′ ratio (18.6 ± 6.7).…”
Section: Discussionmentioning
confidence: 99%
“…Studies show excellent performance metrics with these (Table 3). [21][22][23][24][25][26][27][28][29][30][31][32][33][34] By detecting subtle changes in cardiac structure and function over time, ML algorithms can assist in identifying early indicators of HF. This early detection can facilitate timely interventions and preventative measures, thereby potentially reducing the burden of HF and enhancing patient outcomes.…”
Section: Heart Failure Diagnosismentioning
confidence: 99%
“…29 In another study, a learning model based on CNN and augmented data of heart sounds demonstrated even higher performance metrics (accuracy of 0.987, sensitivity of 0.986, and specificity of 0.988) in establishing an early diagnosis of left ventricular diastolic dysfunction. 26 Heart sound-based AI models present a potentially straightforward and non-invasive method of HF screening, although additional clinical implementation and validation are required.…”
Section: Heart Failure Diagnosismentioning
confidence: 99%